A novel chromone-based as a potential inhibitor of ULK1 that modulates autophagy and induces apoptosis in colon cancer - Shamsudin, Nur Farisya; Leong, Sze Wei; Koeberle, Andreas; Suriya, Utid; Rungrotmongkol, Thanyada; Chia, Suet Lin; Taher, Muhammad; Haris, Muhammad Salahuddin; Alshwyeh, Hussah Abdullah; Alosaimi, Areej A; Mediani, Ahmed; Ilowefah, Muna Abdulsalam; et al. (Taylor and Francis Ltd., 2024)
Aim: Chromones are promising for anticancer drug development. Methods & results: 12 chromone-based compounds were synthesized and tested against cancer cell lines. Compound 8 showed the highest cytotoxicity (LC50 3.2 μM) against colorectal cancer cells, surpassing 5-fluorouracil (LC50 4.2 μM). It suppressed colony formation, induced cell cycle arrest and triggered apoptotic cell death, confirmed by staining and apoptosis markers. Cell death was accompanied by enhanced reactive oxygen species formation and modulation of the autophagic machinery (autophagy marker light chain 3B (LC3B); adenosine monophosphate-activated protein kinase (AMPK); protein kinase B (PKB); UNC-51-like kinase (ULK)-1; and ULK2). Molecular docking and dynamic simulations revealed that compound 8 directly binds to ULK1. Conclusion: Compound 8 is a promising lead for autophagy-modulating anti-colon cancer drugs.